Introduction to Topology : Pure and Applied - Adams, Colin; Franzosa, Robert (Noida, India Pearson, 2009)
Learn the basics of point-set topology with the understanding of its real-world application to a variety of other subjects including science, economics, engineering, and other areas of mathematics. This book introduces topology as an important and fascinating mathematics discipline to retain the readers interest in the subject. It is written in an accessible way for readers to understand the usefulness and importance of the application of topology to other fields. It introduces topology concepts combined with their real-world application to subjects such DNA, heart stimulation, population modeling, cosmology, and computer graphics, and covers topics including knot theory, degree theory, dynamical systems and chaos, graph theory, metric spaces, connectedness, and compactness.
Include References and Index.
Pure and Applied.
Keywords: Topology